Evaluation of intraductal papillary mucinous neoplasms detected incidentally with magnetic resonance cholangiopancreatography - Nalbant, Mustafa Orhan (The European Research Journal, 2023)
Objectives: The aim of this study was to estimate the prevalence of coincidentally found intraductal papillary mucinous neoplasms (IPMNs) and assess their features with magnetic resonance cholangiopancreatography (MRCP) imaging. Methods: The prevalence of incidentally detected IPMN was evaluated in 951 patients who underwent MRCP examination for various indications. MRCP images were assessed to analyze the number, size, location, and internal structure of lesions in patients with IPMN. Furthermore, the association between IPMN prevalence and age and gender was evaluated. Results: IPMN was detected in 102 (10.7%) of 951 patients. Solitary IPMNs were located in different parts of the pancreas: in the uncinate process in 8 (7.8%), in the head and neck in 19 (18.6%), in the corpus in 10 (9.8%), and in the tail in 7 (6.9%) patients. IPMN was multiple in 58 (56.9%) patients. IPMN was identified in 41 (6.18%) patients under 65 years and 61 (21.18%) patients over 65 years, and the variance was statistically substantial (p < 0.001). IPMN diameter was 7.22 ± 4.3 mm in patients under 65 years and 9.21 ± 4.74 mm in those over 65 years, which was statistically significant (p = 0.048). Patients who were older were more likely to have multiple IPMNs (p = 0.010). Conclusions: IPMNs increase in frequency, quantity, and size with age. MRCP is the most essential sequence for determining main pancreatic duct (MPD) involvement or communication, a critical finding for diagnosis. Since MRCP is capable of screening patients at very short intervals, it may be utilized for follow-up imaging in IPMN patients.